Kinesin Light Chains Are Essential for Axonal Transport in Drosophila - Gindhart, Joseph G. (The Rockefeller University Press, 1998)

(untitled)
Kinesin is a heterotetramer composed of two 115-kD heavy chains and two 58-kD light chains. The microtubule motor activity of kinesin is performed by the heavy chains, but the functions of the light chains are poorly understood. Mutations were generated in the Drosophila gene Kinesin light chain (Klc), and the phenotypic consequences of loss of Klc function were analyzed at the behavioral and cellular levels. Loss of Klc function results in progressive lethargy, crawling defects, and paralysis followed by death at the end of the second larval instar. Klc mutant axons contain large aggregates of membranous organelles in segmental nerve axons. These aggregates, or organelle jams (Hurd, D.D., and W.M. Saxton. 1996. Genetics. 144: 1075–1085), contain synaptic vesicle precursors as well as organelles that may be transported by kinesin, kinesin-like protein 68D, and cytoplasmic dynein, thus providing evidence that the loss of Klc function blocks multiple pathways of axonal transport. The similarity of the Klc and Khc (Saxton et al. 1991. Cell 64:1093–1102; Hurd, D.D., and W.M. Saxton. 1996. Genetics 144: 1075–1085) mutant phenotypes indicates that KLC is essential for kinesin function, perhaps by tethering KHC to intracellular cargos or by activating the kinesin motor.